Web commerce security : design and development - Nahari, Hadi.; Krutz, Ronald L. (Indianapolis : Wiley Pub., 2011)
Provides information on designing effective security mechanisms for e-commerce sites, covering such topics as cryptography, authentication, information classification, threats and attacks, and certification.
I: Overview of commerce -- Internet era: E-commerce -- Mobile commerce -- Important "ilities" in Web commerce security -- 2: E-commerce security -- E-commerce basics -- Building blocks: your tools -- System components: what you should implement -- Trust but verify: checking security -- Threats and attacks: what your adversaries do -- Certification: you assurance.
Includes bibliographies and Index.
Keywords: Computer security; Computer networks -- Security measures; Internet -- Security measures; Computer security; Computer networks -- Security measures; Electronic commerce -- Security measures